Reflexões interpretativas: canções para canto e piano de Kilza Setti - Rodrigues, Sandra Regina Zumpano (2011)
This work is part of the research area of Fundamentals Reflections of Arts Master Program at the University of Uberlandia, investigating issues of musical interpretation through the study of text and line song, within a selection of songs for voice and piano of the composer Kilza Setti. The research conducts a review of the scientific interpretation of the musical, the importance of text and vocal line during this process and the factors that may exceed the rational knowledge, reaching the intuitive and emotional. Three authors have been mainstays in elucidating the scope of interpretive questions: STEIN and Spielmann (1996), which discussed the song form, Bakhtin (1979) about the functions of text and Polanyi (1996) about the importance of tacit knowledge. The choice of Kilza Setti gives herself their undoubted importance as a writer and researcher in Brazil. In our view, this research proves to be as significant as it may, in addition to help understanding the interpretive process, contribute to the enrichment of the academic literature on the subject.